2017
DOI: 10.1371/journal.pone.0172738
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic bacterial surface factor polysaccharide A on Bacteroides fragilis inhibits IL-1β-induced inflammation in human fetal enterocytes via toll receptors 2 and 4

Abstract: Colonizing bacteria interacting with the immature, unlike the mature, human intestine favors inflammation over immune homeostasis. As a result, ten percent of premature infants under 1500 grams weight develop an inflammatory necrosis of the intestine after birth, e.g., necrotizing enterocolitis (NEC). NEC is a major health problem in this population causing extensive morbidity and mortality and an enormous expenditure of health care dollars. NEC can be prevented by giving preterm infants their mother’s express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
1
40
0
1
Order By: Relevance
“…Therefore, the discovery of safe and effective preventive methods has become a research hotspot. Symbiotic bacteria often colonize the sterile gut of neonates, which can increase the incidence of NEC (23). TLRs, cell transmembrane receptors of the natural immune system, are critical for pathogen resistance (24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the discovery of safe and effective preventive methods has become a research hotspot. Symbiotic bacteria often colonize the sterile gut of neonates, which can increase the incidence of NEC (23). TLRs, cell transmembrane receptors of the natural immune system, are critical for pathogen resistance (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PSA also inhibited Th17 cell differentiation via suppressing the production of Th17-inducing cytokines. For example, PSA on the surface of Bacteroides fragilis inhibited IL-1β-induced inflammation in human fetal enterocytes via TLR2 and TLR4 [82]. In another study, Bacteroides fragilis-induced macrophage IL-1β secretion was shown to upregulate the expression of hepcidin in the liver, a process dependent on the bone morphogenetic protein signaling pathway [83].…”
Section: Bacteroides Fragilismentioning
confidence: 97%
“…recently reported that fetal enterocytes exposed to PSA produce lower levels of the IL-1β-induced, pro-inflammatory cytokine IL-8, which may play a role in the development of necrotizing enterocolitis in prematurely born infants (Jiang et al, 2017). …”
Section: Microbiome-associated Metabolites That Shape the Immune Systemmentioning
confidence: 99%